The future of the United States-Australia alliance : evolving security strategy in the Indo-Pacific - McDonald, Scott D.; Tan, Andrew T. H. (Andrew Tian Huat) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The United States-Australia alliance has been an important component of the US-led system of alliances that has underpinned regional security in the Indo-Pacific since 1945. However, recent geostrategic developments, in particular the rise of the People's Republic of China, have posed significant challenges to this US-led regional order. In turn, the growing strategic competition between these two great powers has generated challenges to the longstanding US-Australia alliance. Both the US and Australia are confronting a changing strategic environment, and, as a result, the alliance needs to respond to the challenges that they face. The US needs to understand the challenges and risks to this vital relationship, which is growing in importance, and take steps to manage it. On its part, Australia must clearly identify its core common interests with the US and start exploring what more it needs to do to attain its stated policy preferences. This book consists of chapters exploring US and Australian perspectives of the Indo-Pacific, the evolution of Australia-US strategic and defence cooperation, and the future of the relationship. Written by a joint US-Australia team, the volume is aimed at academics, analysts, students and the security and business communities"--
The United States-Australia alliance / Scott D. McDonald and Andrew T.H. Tan -- The strategic environment of the US-Australia alliance in the Indo-Pacific era / Alexander L. Vuving -- The United States' security perspectives in the Asia-Pacific and the value of the alliance with Australia / Paul J. Smith -- Security threats and challenges to Australia / Andrew T.H. Tan -- The common interests that bind the United States and Australia / Bates Gill -- The evolution of the US-Australia strategic relationship / Shannon Brandt Ford -- Defence co-operation between Australia and the United States / Alan Bloomfield -- China-US-Australia : redefining the strategic triangle / Adam Lockyer, Scott D. McDonald and Yves Heng-Lim -- The US-Australian alliance and its implications for Australian defence strategy and procurement / Fred Smith, Yves-Heng Lim and Adam Lockyer -- The future of Australia-US strategic and defence cooperation : an Australian perspective / Andrew O'Neil -- The future of Australia-US strategic and defence cooperation : a US perspective / Scott D. McDonald.
OCLC-licensed vendor bibliographic record.
Keywords: Geopolitics -- Indo-Pacific Region; United States -- Foreign relations -- Australia; Australia -- Foreign relations -- United States; Indo-Pacific Region -- Strategic aspects; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Arms Control; POLITICAL SCIENCE / International Relations / General